1987
DOI: 10.1104/pp.83.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Partial Kinetic and Physical Characterization of Two Chloroplast-Localized NADP-Specific Glutamate Dehydrogenase Isoenzymes and Their Preferential Accumulation in Chlorella sorokiniana Cells Cultured at Low or High Ammonium Levels

Abstract: Two ammonium-inducible, chloroplast-localized NADP-specific glutamate dehydrogenase isoenzymes were purified to homogeneity from Chlorella sorokiniana. These isoenzymes were homopolymers of either a-or a-subunits with molecular weights of 55,500 or 53,000, respectively.The a-isoenzyme was preferentially induced at low ammonium concentrations (2 millimolar or lower), whereas only the f,-isoenzyme accumulated after cells were fully induced (120 minutes) at high ammonium concentrations (29 millimolar 53,000 (4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…There have been reports of a similar inducible NADPH-GDH in several microorganisms (Tischner & Lorenzen, 1980;Everest & Syrett, 1983;Martin, Msatef & Botton, 1983;Ahmad & Hellebust, 19866;Bascomb & Schmidt, 1987;Jennings, 1989;Ahmad et al, 1990;Schwartz, Kusnan & Fock, 1991). Interestingly, in the green alga Stichococcus bacillaris (Everest & Syrett, 1983 ;Ahmad & Hellebust, 1986ft) NADPH-GDH exhibits a normal rate response curve for ammonium concentration with a single Kv alue of 1-2 mM, whereas in another green alga, Chlorella sorokiniana (Tischner, 1984;Bascomb & Schmidt, 1987), The NADPH-GDH exhibits dual kinetics with respect to ammonium concentration, showing a low K^^ of < 5 mM and a high K,,, of > 20 mM. It has been suggested that the high Kv alue for ammonium in the kinetic measurements of NADPH-GDH in C. sorokiniana is associated with post-translational modifications of the low K^.ê nzyme that occur when the culture ages or when the concentration of ammonium in the medium is high (Prunkard et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been reports of a similar inducible NADPH-GDH in several microorganisms (Tischner & Lorenzen, 1980;Everest & Syrett, 1983;Martin, Msatef & Botton, 1983;Ahmad & Hellebust, 19866;Bascomb & Schmidt, 1987;Jennings, 1989;Ahmad et al, 1990;Schwartz, Kusnan & Fock, 1991). Interestingly, in the green alga Stichococcus bacillaris (Everest & Syrett, 1983 ;Ahmad & Hellebust, 1986ft) NADPH-GDH exhibits a normal rate response curve for ammonium concentration with a single Kv alue of 1-2 mM, whereas in another green alga, Chlorella sorokiniana (Tischner, 1984;Bascomb & Schmidt, 1987), The NADPH-GDH exhibits dual kinetics with respect to ammonium concentration, showing a low K^^ of < 5 mM and a high K,,, of > 20 mM. It has been suggested that the high Kv alue for ammonium in the kinetic measurements of NADPH-GDH in C. sorokiniana is associated with post-translational modifications of the low K^.ê nzyme that occur when the culture ages or when the concentration of ammonium in the medium is high (Prunkard et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhibition of GS by methionine sulphoximine (MSX) has little effect on the assimilation of ammonium by C. autotrophica (Ahmad & Hellebust 1985a, 1988a. Interestingly, NADPH-GDH in Chlorella sorokiniana shows a complex pattern of accumulation and also an alteration of its affinity for ammonium under different growth conditions (Tischner & Lorenzen, 1980;Tischner, 1984;Bascomb & Schmidt, 1987). It would therefore be interesting to examine the kinetic properties of NADPH-GDH from C autotrophica under various growth conditions.…”
mentioning
confidence: 99%
“…The same size precursor-protein is synthesized in vitro by poly(A)+RNA isolated from cells accumulating a-and (3-isoenzymes or only the (3-isoenzyme (2, 1 1). Cell extracts from C. sorokiniana have been shown (2) to process in vitro the 58,500 D precursor-protein(s) to a-or ,8-subunits with mol wt of 55,500 and 53,000, respectively. The a-and (3-subunits have been shown to be in active holoenzymes (homopolymers) localized in the chloroplast (2,11).…”
Section: Methodsmentioning
confidence: 99%
“…an amino acid), utilized during protein synthesis, might protect the NADP-GDH from degradation. When (2,3,10,11,13,20) from this laboratory, have been summarized and formulated into a working model/hypothesis for the regulation of expression of the gene(s) encoding the NADP-GDH isoenzymes in C. sorokiniana (Fig. 6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation